The effectiveness of normal birth e-module on increasing nursing students' learning satisfaction - Jamaludin, Hasna Nurul Naafiah; Susanti, Raini Diah; Agustina, Habsyah Saparidah; Mulyana, Aep Maulid (Universitas Airlangga, 2023)
Introduction: E-modules are information technology-based modifications of conventional modules. Students learning satisfaction can be used to gauge learning success. Learning satisfaction is the value of comparing the level of reality with the level of expectation in learning. This study aims to determine the effectiveness of the normal birth e-module in increasing nursing student learning satisfaction.Methods: Pre-experimental with a one-shot case study design with data from online survey results using the E-Module Satisfaction Questionnaire instrument. The population of this study was 244 active students of the Faculty of Nursing, Universitas Padjadjaran, who had completed the maternity course using the normal birth e-module. As many as 46 people were willing to be respondents and fill out the level of learning satisfaction questionnaire. The study samples were determined by G-Power and data analysis using the Pearson Correlation test and the R square test or the Coefficient of Determination.Results: Overall, the level of learning satisfaction of nursing students who use the normal birth e-module is very satisfactory/high, with an average of 4.51% in the range of 4.5 - 5.0. The percentage of the results of the assessment of all respondents was dissatisfied (0.2%), quite satisfied (5%), satisfied (38.7%), and very satisfied (56.1%). However, 2.2% or 1 out of 46 participants reported dissatisfaction with the respondent's understanding. The coefficient of determination or R square test of 0.876 or 87.6% is in the 0.8 – 0.99 (very effective).Conclusions: The use of the Normal Birth E-Module is very effective as a learning method that can increase the level of learning satisfaction of nursing students.Keywords: e-module; learning satisfaction; normal birth; nursing students